2012
DOI: 10.1097/brs.0b013e3182217ab5
|View full text |Cite
|
Sign up to set email alerts
|

Major Complications in Revision Adult Deformity Surgery

Abstract: Overall, 34.4% of patients experienced major complications after long revision fusion surgery. Different risk factors were identified for perioperative versus follow-up complications. The occurrence of a follow-up, not but perioperative, major complication seemed to have a negative impact on ultimate clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(50 citation statements)
references
References 16 publications
2
48
0
Order By: Relevance
“…Schwab et al [17] reported major perioperative complication rate in the order of 8.4 %. Cho et al [18] reported major complications in 34.3 % of the patients undergoing revision deformity surgery. While most of the literature reports an average complication rate of about 40 %, the overall surgeon reported complication rate in the SRS registry remains around 13.4 % [5].…”
Section: Discussionmentioning
confidence: 99%
“…Schwab et al [17] reported major perioperative complication rate in the order of 8.4 %. Cho et al [18] reported major complications in 34.3 % of the patients undergoing revision deformity surgery. While most of the literature reports an average complication rate of about 40 %, the overall surgeon reported complication rate in the SRS registry remains around 13.4 % [5].…”
Section: Discussionmentioning
confidence: 99%
“…6,7,1012,15 The combination of an aging population and increasing number of spine fusion procedures results in an increasing number of patients with adult deformities, as well as an increasingly complex revision burden. 13,14 With the rising revision burden, the diagnosis of fixed sagittal malalignment is increasingly common.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of ''older'' age being associated with higher risk of complication has been described in trauma [29], degeneration [28], revision [30], or tumor [7] series. Similarly, the current study showed that older age was an independent risk factor for two or more complications.…”
Section: Discussionmentioning
confidence: 99%